Maternal, Fetal and Service-Related Risk Factors for Stillbirths During Conflict Situation, Yemen, 2015-2016 - Al-Shahethi, Ahmed Hamood; Zaki, Rafdzah Ahmad; Al-Serouri, Abdulwahed Abdulgabar; Bulgiba, Awang (Journal of Maternal and Child Health, 2023)
Background: Stillbirth is a silent traumatic canker, which is a major concern to individuals, health institutions countries worldwide and continues to be a major global problem responsible for nearly three million deaths each year. To estimate the stillbirth rate (SBR) and to identify the potential risk factors for stillbirth. Subjects and Method: A community-based prospective cohort study was undertaken between August 2015 and December 2016 in which 980 pregnant women in Sana’a city of Yemen were identified. A multi-stage cluster sampling was used to select participants from community households. The independent variables were socio-demographic, prenatal and past obstetric, special habit, birth and fetal. The dependent variable was stillbirth. The data collection of this study used a questionnaire. Binomial regression together with generalized linear models, were employed in this study. Results: The results identified that the stillbirth rate (SBR) was presently between 46.2 per 1000 and 45.2 per 1000 cases. The multivariable analysis identified teenage mothers aged < 20 years, with their first childbirth, had a (aOR= 3.70; 95% CI= 1.76 to 7.76; p<0.001) women with anemia (aOR = 2.23; 95% CI= 1.67 to 2.98; p<0.001), smoking snuff (aOR = 4.27; 95% CI= 1.17 to 15.55; p= 0.028), prolonged labor (> 24 hours) (aOR= 2.02; 95% CI= 1.38 to 2.96; p< 0.001), prolonged rupture of membranes (≥ 24 hours) (aOR= 2.22; 95% CI= 1.66 to 2.98; p<0.001), fetal mal-position (aOR= 4.60; 95% CI= 2.97 to 7.12; p<0.001), low birth weight (aOR= 14.90; 95% CI= 4.30 to 51.75; p<0.001) and fetal gestational age (in weeks) (aOR = 5.60; 95% CI= 2.52 to 12.41; p<0.001). These factors were associated with an increased risk of stillbirths. Conclusion: This study is encouraging pregnant women to deliver at health facilities, providing better management of obstetrical complications, proper antenatal care, and prompt referral services are essential for the reduction of stillbirths in Yemen. Keywords: stillbirth, risk factors, community-based study, cohort study, Sana’a city, Yemen Correspondence:Ahmed H. Al-Shahethi. National Center for Epidemiology and Diseases Surveillance, Ministry of Public Health and Population, Yemen. P.O. box: 299. Fax: +9671564720. Phone: +967771922712. Email: alshahethi71@yahoo.com, ahmedhamood71@gmail.com.